Elaboração do storymaps para divulgação de dados da Bacia Hidrográfica do Rio Tibagi - Manchur, Josiane (2023)
The efficient management of water resources is crucial to ensuring water sustainability and meeting the needs of society, in addition to protecting the environment. Publicizing the actions developed can also be important in raising awareness among the population. Today's society, highly connected with technological resources, favors this type of action, aiming to educate and inform the public about the importance of conserving natural resources. However, many initiatives do not reach public knowledge. With the purpose of expanding the dissemination of water resources conservation actions, mainly through free access tools on the internet, this work focused on the use of WebGIS technology, with emphasis on ArcGIS StoryMaps. The main objective was to explore the potential of WebGIS, specifically ArcGIS StoryMaps, as a platform for disseminating information related to the use of water resources, for the purpose of raising awareness and promoting their conservation in the Tibagi River Basin. The methodology consisted of: a) a qualitative approach of an exploratory nature, examining water resources management policies; b) collection and compilation of various types of social and environmental data, including specific, matrix and alphanumeric information from the area in question, which were imported into the QGIS 3.22 software; and, c) the use of WebGIS StoryMaps to disseminate information related to water use, awareness and conservation of the Tibagi River. The results showed that WebGIS StoryMaps, with its variety of interactive tools, such as maps, images and videos, allowed information to be transmitted in an engaging and accessible way to the general public. This approach contributed significantly to the dissemination of knowledge among the population, highlighting the need for conservation and preservation of our natural resources.